The effect of surgical treatment on the quality of life of patients with gastroesophageal reflux disease - Łagoda, Katarzyna; Sierżantowicz, Regina; Jurkowska, Grażyna (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2015)
Gastroesophageal reflux disease (GERD) is a chronic disease involving passage of gastric contents to the oesophagus due to temporary or permanent insufficiency of inferior sphincter of the oesophagus. It is diagnosed in 10-20% of inhabitants of the United States and Western Europe. In of patients, the ailments recur quite often, they can differ in intensity, from slight to very persistent ones, and they require pharmacological treatment and sometimes also surgical treatment. The chronic and recurrent character of the ailments has a negative impact on the physical and mental state of the patients, changes their lifestyle, limits social contacts and life activity. Many clinical studies assess QOL of patients with GERD and the effect of specific therapeutic procedures on the patients’ physical and mental state, intensity and frequency of symptoms. The findings show that surgical treatment of GERD helps to alleviate the ailments and has a positive impact on the patients’ QOL.